Strategi Meningkatkan Peran Kepolisian dalam Kerjasama Internasional: Studi Pada Atase Dan Staf Teknis Kepolisian Negara Republik Indonesia - Tlonaen, Alex Willem; Asropi, Asropi; Giyanto, Bambang (International Journal of Demos (IJD), 2022)
AbstractThe rapid increase in technology has led to the emergence of an era of globalization that creates a world without boundaries, where people can interact with each other without any obstacles. However, in the field of security itself, this has then led to the emergence of transnational crimes in various countries, including Indonesia. This study aims to analyze the role of the Representatives of the Indonesian National Police in the country of assignment in order to realize the international cooperation of the Indonesian National Police. The approach in this research is qualitative with descriptive method. The research data was obtained from the results of research and previous studies, as well as the results of interviews with several sources. The results of this study indicate that in general, the Attache of the Indonesian National Police and the Technical Staff of the State Police of the Republic of Indonesia have understood the purpose of their assignment while abroad. However, unfortunately, the recruitment and selection of candidates for the Attache of the Indonesian National Police and the Technical Staff of the State Police of the Republic of Indonesia is still not good. Then the facilities and infrastructure to be able to support the main tasks are still not adequate. Finally, the strategies and efforts that have been made by the Indonesian National Police to increase the role of the Attache of Indonesian National Police AttachÃ© and the Indonesian National Police Technical Staff are still not optimal.Keywords: Strategy, Indonesian National Police, International Cooperation, Attache and Technical Staff of the Indonesian National Police.Â AbstrakPeningkatan yang cukup pesat di dalam bidang teknologi menyebabkan munculnya era globalisasi yang menciptakan dunia tanpa batas, di mana orang-orang dapat berinteraksi satu sama lainnya tanpa adanya halangan. Namun dalam bidang keamanan sendiri, hal ini kemudian menyebabkan munculnya kejahatan transnasional di berbagai negara, termasuk Indonesia. Penelitian ini bertujuan untuk menganalisis peran Perwakilan Polri di negara penugasan dalam rangka mewujudkan Kerjasama internasional Polri. Pendekatan dalam penelitian ini adalah kualitatif dengan metode deskriptif. Data penelitian diperoleh dari hasil penelitian dan studi terdahulu, serta hasil wawancara dengan beberapa sumber. Hasil penelitian ini menunukkan bahwa secara umum, Atase Polri dan Staf Teknis Polri telah memahami tujuan penugasan mereka selama di luar negeri. Namun sayangnya pelaksanaan rekrutmen dan seleksi dari calon Atase Polri dan Staf Teknis Polri masih belum baik. Kemudian sarana dan prasarana untuk dapat mendukung tugas pokok masih juga belum memadai. Terakhir strategi dan upaya yang telah dilakukan oleh pihak Polri untuk dapat meningkatkan peranan Atase Polri dan Staf Teknis Polri masih belum maksimal.Kata Kunci: Strategi, Kepolisian Negara Republik Indonesia, Kerja Sama Internasional, Atase dan Staf Teknis Kepolisian Negara Republik Indonesia.